Examining Bank Health Ratings and Their Impact on Non-Performing Financing in Indonesian Islamic Banks - Suci Rahmadani (Journal of Law and Economics, 2025)
The relationship between Islamic Commercial Bank health indicators and non-performing financing requires careful examination amid recent economic volatility. Researchers analyzed quarterly financial data from eleven Indonesian Islamic Commercial Banks spanning 2019-2024 using panel data regression through E-views software, employing the RGEC framework with Financing to Deposit Ratio (FDR), Return on Equity (ROE), Operating Expense to Operating Income Ratio (BOPO), and Capital Adequacy Ratio (CAR) as independent variables, while Non-Performing Financing (NPF) served as the dependent variable. Statistical analysis reveals that FDR, ROE, BOPO, and CAR jointly lack predictive power for NPF variations, with the model explaining merely 3.079% of variance (Adjusted R-Square). Individual variable testing identifies FDR as the sole significant predictor, demonstrating an inverse relationship with NPF—higher financing distribution correlates with lower default rates when lending remains selective, whereas ROE, BOPO, and CAR show no meaningful association with non-performing financing levels. These findings challenge conventional assumptions about financial ratio utility in predicting credit quality deterioration, as the model's weak explanatory power suggests internal financial metrics alone offer insufficient understanding of NPF dynamics. Future research should integrate external determinants including macroeconomic indicators, regulatory policy shifts, and institutional risk management practices to develop more robust predictive frameworks for Islamic banking credit risk.